2008
DOI: 10.1093/aob/mcn055
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of the Woody Medicago Species (Section Dendrotelis) Assessed by Molecular Cytogenetic Analyses

Abstract: FISH results support the close taxonomic interrelationship between M. arborea and M. strasseri. In these tetraploid species, NOR loci have experienced a diploidization event through physical loss of sequences, a cytogenetic feature so far not reported in other species of the genus. The high number of rDNA loci and GISH results support the specific status for the hexaploid M. citrina, and it is suggested that this species is not an autopolyploid derivative of M. arborea or M. strasseri. Further, molecular cytog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Previously, it was reported that the polymorphism distribution of the rDNAs obtained from phylogenetic analyses (the outgroup was C. metuliferus ) correlated well with the results obtained from rDNA FISH patterns [Rosato et al, 2008]. In another phylogenetic study, it was suggested that C. metuliferus may be derived from the African Cucumis species, and thus may be a putative diploid ancestral species of the C. heptadactylus group [Sebastian et al, 2010].…”
Section: Discussionsupporting
confidence: 57%
“…Previously, it was reported that the polymorphism distribution of the rDNAs obtained from phylogenetic analyses (the outgroup was C. metuliferus ) correlated well with the results obtained from rDNA FISH patterns [Rosato et al, 2008]. In another phylogenetic study, it was suggested that C. metuliferus may be derived from the African Cucumis species, and thus may be a putative diploid ancestral species of the C. heptadactylus group [Sebastian et al, 2010].…”
Section: Discussionsupporting
confidence: 57%
“…We followed the in situ hybridization protocol used by Rosato et al (2008), and probe detection was conducted using the method of Hanson et al (1995) with minor modifications. After detection, the chromosomes were mounted in Vectashield antifade (Vector Laboratories Inc., Burlingame, CA, USA) with 5 mg/ml of 4¢,6-diamidino-2-phenylindole used as a counterstain.…”
Section: Cytogenetic Analysesmentioning
confidence: 99%
“…FISH was carried out according to Chiavarino et al (2000) with some modifications (Rosato et al, 2008). Pretreatment of chromosome preparations involved incubation with RNase A (1 mg/mL) in 2X SSC for 1 h at 37 °C; afterwards, the slides were rinsed three times for 5 min in 2X SSC.…”
Section: Probe Labeling Of 5s and 45s Rrna Genes And Fishmentioning
confidence: 99%